Developing the Resilience of Pressure Index on Islamic Banking in Indonesia - Malik, Satria (Jurnal Ekonomi Indonesia, 2019)
Islamic banking is a component of financial institutions and the global financial system. Although the size of Islamic banking with conventional banking is smaller, the vulnerability in Islamic banking always within it. This is due to the presence of various financial risks that follow the credit cycle. Besides that, there is no one who concludes clearly that Islamic banking is more resilient than conventional banking. Therefore, some regulations need to be issued to maintain the balance and adaptive aspects of Islamic banking resilience. So that this research aims to measure the optimal level of pressure because of financing activities. This research uses an early warning system approach to estimate optimal pressure levels in Islamic banking caused by funding activities using monthly data from 2010 to 2018. The findings of this research indicate that the optimal level of pressure in Islamic banking is basically to maintain a certain financing risk and provide an optimal level caused by external shocks. This research found that the optimal level of pressure is between - 0.41 to 0.08. Finally, this research concludes that the resilience of Islamic banking in Indonesia requires a balanced asset-financing allocation by lowering non-performing financing, increasing liquid assets, and sound capital adequacy.